Efeito da triiodotironina (T3) na diferenciação osteogênica in vitro de células tronco mesenquimais da medula óssea de ratas - Jankerle Neves Boeloni (2008)
The objective of this study was to verify the dose-dependent effect of T3 in the osteogenic differentiation of MSC of female rats. Long bones (femur and tibia) from female Wistar rats (30 days) were obtained for the extraction of MSC from bone marrow, expanded in culture in enriched DMEM supplemented with fetal calf serum at 37ºC and 5% of CO2. After four passages, 1x105 MSC were cultivated in triplicate in enriched DMEM added to ascorbic acid, -glycerophosphate and dexamethasone for 7, 14 and 21 days with T3 (doses of 10-3nM, 10-2nM, 1nM and 100 nM) and without T3 (control). The phenotypic characterization of the cells was accomplished before the osteogenic differentiation by flow cytometry. During the osteogenic differentiation, the alkaline phosphatase activity was evaluated by the BCIP-NBT assay and the capacity of conversion of MTT in formazan crystals, both by espectrofotometry. The collagen was stained with sirius red, dosed in spectrophotometer and appraised in polarization microscopy. Mineralized nodules were stained by Von Kossa for evaluation of the number of nodules/field and mean nodules diameter. The means were compared by the SNK test. Before the osteogenic differentiation, the cells were positive for CD73 (93,99%), CD54 (95,10%) and CD90 (86,77%) and were negative for CD45 (96,94%). The dose of 100nM showed negative effect in the MSC osteogenic differentiation, with less collagen synthesis in comparison to the control and formation of countless calcium phosphate crystals. The 10-3nM dose showed collagen synthesis, alkaline phosphatase activity and mineralized nodules number higher then the control and similar to the 10-2nM dose. Nevertheless, the 10-2nM dose demonstrated better results under the MSC osteogenic differentiation, with more MTT reduction, better collagen maturation and larger mean diameter of the mineralized nodules. It was concluded that the T3 effect in the MSC in vitro differentiation is dose-dependent and the 10-2nM dose promotes better bone marrow MSC osteogenic differentiation